Board of Director Characteristics and Audit Report Lag: Australian Evidence - Singh, Harjinder; Sultana, Nigar (Virtus Interpress, 2012)
This study examines whether board of director's independence, financial expertise, gender, corporate governance experience and diligence impact the audit report lag exhibited by Australian publicly listed firms. Using a pooled sample of 500 firm-year observations obtained from the Australian Securities Exchange for the period 2004 to 2008, this study finds evidence that board member independence, board member financial expertise and, to a lesser extent, board member corporate governance experience are the most significant measures of audit report lag, board characteristics and control variables. Findings from this study clearly imply that boards play a substantial role in reducing audit report lag. Results imply that legislative and regulatory requirements, both in Australian and overseas, stipulating board member independence and financial expertise requirements are effective in improving the integrity of financial reporting, a key component of which is timeless of reporting (encapsulated by audit report lag). In addition, an additional board characteristic that regulators should consider promoting among firms is board member corporate governance experience. Results from this study, therefore, have clear implications not only for regulators but also for key stakeholders such as shareholders and management.